Perancangan Aplikasi Surat Keteranggan Pengantar Ijazasah Berbasis Web - Sukarna, Royan Habibie; Krisdianto, Nanang; Hilman, Mohamad; Holilah, Holilah; Januriana, Andi Moch; Umam, Ahmad Khaerul (Teknik Informatika Fakultas Ilmu Komputer, 2024)
This study explains how to create and implement a web-based application for Certificate of Introduction to Diplomas (SKPI) using the Laravel framework and the Extreme Programming (XP) method. With SKPI as a confirmation of competency after graduation, this application aims to record student competency during the course. The XP method is used to ensure flexibility, collaboration and sustainability in application development. The Laravel framework was chosen for its ease of use and strength in backend/API creation, which allows integration with other applications. The research results show that the SKPI application was successfully created with features that meet the need for recording and verifying student competency. This research contributes to a practical understanding of web-based application development with a focus on student competency track records